Exosome-mediated transfer of miR-222 is sufficient to increase tumor malignancy in melanoma. Issue 1 (December 2016) - Felicetti, Federica; Feo, Alessandra; Coscia, Carolina; Puglisi, Rossella; Pedini, Francesca; Pasquini, Luca; Bellenghi, Maria; Errico, Maria; Pagani, Elena; Carè, Alessandra
Abstract Background Growing evidence is showing that metastatic cell populations are able to transfer their characteristics to less malignant cells. Exosomes (EXOs) are membrane vesicles of endocytic origin able to convey their cargo of mRNAs, microRNAs (miRs), proteins and lipids from donors to proximal as well as distant acceptor cells. Our previous results indicated that miR-221&222 are key factors for melanoma development and dissemination. The aim of this study was to verify whether the tumorigenic properties associated with miR-222 overexpression can be also propagated by miR-222-containing EXOs. Methods EXOs were isolated by UltraCentrifugation or Exoquick-TC® methods. Preparations of melanoma-derived vesicles were characterized by using the Nanosight™ technology and the expression of exosome markers analyzed by western blot. The expression levels of endogenous and exosomal miRNAs were examined by real time PCR. Confocal microscopy was used to evaluate transfer and uptake of microvesicles from donor to recipient cells. The functional significance of exosomal miR-222 was estimated by analyzing the vessel-like process formation, as well as cell cycle rates, invasive and chemotactic capabilities. Results Besides microvesicle marker characterization, we evidenced that miR-222 exosomal expression mostly reflected its abundance in the cells of origin, correctly paralleled by repression of its target genes, such as p27Kip1, and induction of the PI3K/AKT pathway, thus confirming its functional implication in cancer. The possible differential significance of PI3K/AKT blockade was assessed by using the BKM120 inhibitor in miR-222-transduced cell lines. In addition, in vitro cultures showed that vesicles released by miR-222-overexpressing cells were able to transfer miR-222-dependent malignancy when taken-up by recipient primary melanomas. Results were confirmed by antagomiR-221&222 treatments and by functional observations after internalization of EXOs devoid of these miRs. Conclusion All together these data, besides generally confirming the role of miR-222 in melanoma tumorigenesis, supported its responsibility in the exosome-associated melanoma properties, thus further indicating this miR as potential diagnostic and prognostic biomarker and its abrogation as a future therapeutic option.